Molecular diffusion of ultrafine nickel catalysts, based on silica gel, depending on the temperature; ATPC 2013. The 10th Asian Thermophysical Properties Conference, September 29 - October 3, 2013, Ramada Plaza Hotel, Jeju, Korea; Poster Session II - Khushvaktov (Khushvakhtov) A. A. Alisher Asanovich (2013, 2013)
В фонде НТБ ТПУ отсутствует